Extrachromosomal circular DNA in cancer: history, current knowledge, and methods. Issue 7 (July 2022) - Noer, Julie B.; Hørsdal, Oskar K.; Xiang, Xi; Luo, Yonglun; Regenberg, Birgitte
Abstract : Extrachromosomal circular DNA (eccDNA) is a closed-circle, nuclear, nonplasmid DNA molecule found in all tested eukaryotes. eccDNA plays important roles in cancer pathogenesis, evolution of tumor heterogeneity, and therapeutic resistance. It is known under many names, including very large cancer-specific circular extrachromosomal DNA (ecDNA), which carries oncogenes and is often amplified in cancer cells. Our understanding of eccDNA has historically been limited and fragmented. To provide better a context of new and previous research on eccDNA, in this review we give an overview of the various names given to eccDNA at different times. We describe the different mechanisms for formation of eccDNA and the methods used to study eccDNA thus far. Finally, we explore the potential clinical value of eccDNA. Highlights: Extrachromosomal circular DNA (eccDNA) has been described under different names at various times since the 1960s. eccDNA can be formed in cells as a result of various cellular events and DNA repair mechanisms in different contexts. Large eccDNA in cancer is also called circular extrachromosomal DNA (ecDNA). It can amplify oncogenes rapidly and contribute to their higher expression by more accessible chromatin and novel contacts with enhancers. NGS-based methods have greatly accelerated our knowledge of eccDNA in recent years; however, more development of cell and animal models for functional studies is needed. eccDNA and ecDNA hold promise as targets for treatment or diagnostic procedures, but the clinical value still needs to be determined.